INTEREST IN SCIENTIFIC AND PEDAGOGICAL KNOWLEDGE AS A COMPONENT PROFESSIONAL INTEREST MODERN TEACHER - L.I. Kramarenko (Academy of Cognitive and Natural Sciences, 2004)
Interest to pedagogic-scientific knowledge are considered as an object of professional interest, its main properties and role in the professional training of future teachers are characterized in the article.